Engineering transport by concatenated maps - Schell, Torben; Sadgrove, Mark; Nakagawa, Ken'ichi; Wimberger, Sandro (Fluctuation and noise letters, 2013)
We present a generalized kick rotor model in which the phase of the kick can vary from kick to kick. This additional freedom allows one to control the transport in phase space. For a specific choice of kick-to-kick phases, we predict novel forms of accelerator modes which are potentially of high relevance for future experimental studies.
Gesehen am 04.02.2022